Civic education and ideologization in cuban elementary school - Garcés Marrero, Roberto; Aguilar Santos, Jeisil (Revista Colombiana de Ciencias Sociales, 2026)
This article analyzes the role of Cuban educational institutions and their curriculum in shaping citizenship. Using discourse analysis methodology, the civic education texts for 5th and 6th grade are examined to identify how the figure of the Cuban citizen is constructed within a socialist political system. The findings show strong ideologization and normalization, promoting a dichotomous worldview and limiting the development of critical thinking. The texts reinforce an ideologized view of citizenship, where homeland and socialism are intrinsically linked. They promote conformity and obedience to a specific political regime, with a notable absence of terms related to democracy and peace, and a prevalence of concepts like revolution and work. This limits critical thinking and diversity of perspectives.